Python in a nutshell - Martelli, Alex; Ravenscroft, Anna Martelli; Holden, Steve, 1950- (In a nutshell (O'Reilly & Associates), 2017)
This book provides a quick reference to the language, including Python 3.5, 2.7 and highlights of 3.6. It covers a wide range of application areas, including web and network programming, XML handling, database interactions, and high-speed numeric computing